Kapasitas Penyerapan Limbah Fosfat oleh Dua Tanaman Air yang Melimpah di Bali (Eichornia crassipes dan Salvinia molesta) - Kintanijaya Kintanijaya; Ima Yudha Perwira; Ni Putu Putri Wijayanti (Bumi Lestari Journal of Environment, 2021)
Phosphate is known to be one of many pollutants in the aquatic environment causing environmental degradation. This study aimed to know the absorption rate of phosphate by two most abundant water plant in Bali (Eichornia crassipes and Salvinia molesta). This study used three treatments: treatment A (using Eichornia crassipes), treatment B (using Salvinia molesta), and treatment C (combination of both plants). Each treatment was performed in triplicate. The phytoremediation process was carried out in 14 days, and the measurement of phosphate in the water was carried out in every 7 days (day 1, day 7, and day 14). The other parameters measured in this study were: temperature, pH and Total Dissolved Solid (TDS). The concentration of phosphate was measured using Hanna HI-713 KIT, while temperature, pH and TDS were measured using: thermometer, pH meter, and TDS meter, respectively. Result showed that the most efficient treatment to absorb the phosphate in the water was shown by treatment using Eichornia crassipes (up to 37.4%).